Tunable luminescence and energy transfer properties of MgY4Si3O13: Ce3+, Tb3+, Eu3+ phosphors. Issue 18 (15th December 2017) - Wang, Wanrong; Jin, Ye; Yan, Shan; Yang, Yuanqing; Liu, Yali; Xiang, Guotao
Abstract: The tricolor-emitting MgY4 Si3 O13 : Ce 3+, Tb 3+, Eu 3+ phosphors for ultraviolet-LED have been prepared via a high-temperature solid-state method. X-ray diffraction, photoluminescence emission, excitation spectra and fluorescence lifetime were utilized to characterize the structure and the properties of synthesized samples. Two different lattice sites for Ce 3+ are occupied from the host structure and the normalized PL and PLE spectra. The emissions of single-doped Ce 3+ /Tb 3+ /Eu 3+ are located in blue, green and red region, respectively. The energy transfer from Ce 3+ to Tb 3+ and from Tb 3+ to Eu 3+ has been validated by spectra and decay curves and the energy transfer mode from Tb 3+ to Eu 3+ was calculated to be electric dipole-dipole interactions. By adjusting the content of Tb 3+ and Eu 3+ in MgY4 Si3 O13 : Ce 3+, Tb 3+, Eu 3+, the CIE coordinates can be changed from blue to green and eventually generate white light under UV excitation. All the results indicate that the MgY4 Si3 O13 : Ce 3+, Tb 3+, Eu 3+ phosphors are potential candidates in the application of UV-WLEDs.